2018
DOI: 10.1371/journal.pntd.0006255
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of Leishmania major from an endemic to a non-endemic region posed a public health threat in Iraq from 2014-2017: Epidemiological, molecular and phylogenetic studies

Abstract: BackgroundCutaneous leishmaniasis (CL) is a neglected worldwide, zoonotic, vector-borne, tropical disease that is a threat to public health. This threat may spread from endemic to non-endemic areas. Current research has exploited epidemiological, molecular and phylogenetical studies to determine the danger of an outbreak of CL in the borderline area between northern and central Iraq from 2014–2017.Methodology/Principal findingsFor the first time, using sequence analysis of the cytochrome b gene, the occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Leshmania major is the main genotype causing CL in Iraq. 15 The same genotypes were reported in Iran. 16 However, the cure rate in Iran ranged from 25% to 80%.…”
Section: Discussionsupporting
confidence: 59%
“…Leshmania major is the main genotype causing CL in Iraq. 15 The same genotypes were reported in Iran. 16 However, the cure rate in Iran ranged from 25% to 80%.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, the opening of the border between Iran and Iraq appears to have played an important role in the spread and the transmission of Leishmania strains between the two countries (128). High genetic similarity between a newly emerged Iraqi L. major strain and an Iranian strain support this hypothesis (101). As a vector-borne disease with two predominant vectors, P. papatasi (ZCL) and P. sergenti (ACL), and animal and human reservoirs, respectively, multiple factors will affect disease prevalence and epidemic proneness that will be favor one species over another or be common to both.…”
Section: Discussionmentioning
confidence: 93%
“…The civil war in Syria is a striking example with large numbers from highly CL endemic foci causing epidemics in neighboring countries, as well as the emergence of new foci of CL caused by nonindigenous Leishmania species. Similarly, since 2014 in Iraq, population displacement has led to CL outbreaks in non-endemic areas between north and central Iraq (101). CL is found more commonly in poor and marginalized populations due to a variety of factors that include small overcrowded poorly constructed dwellings with no screens on windows, poor nutritional status, lack of personal protection against insect bites, and the presence of garbage collection areas (141).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Al-Bajalan et al . [12] observed that the incidence of CL was 27.5 per 100,000 populations, in a study carried out in Garmian area, Iraq, bordering with Iran. By active case detection, more CL cases may be identified since many patients never seek medical care.…”
Section: Discussionmentioning
confidence: 99%